Digital inequalities among public university students in Angola - Barbante, Cesário; Oliveira, Lia (Millenium - Journal of Education, Technologies, and Health, 2025)
Introduction: Considering the growing use of digital technologies in education, ensuring access to this resource has become essential. This article focuses on the effort to align with the sustainability principles of the UN 2030 Agenda, with regard to reducing inequalities. Objective: The present study aims to measure the levels of inequality in access to digital technologies and the internet among public university students in Angola. Methods: In this way, we seek to answer the following questions: 1) What are the levels of access to digital technologies and the internet among students? 2) Is the student's socioeconomic condition a factor in inequality of digital skills? 3) Are students from rural areas (geographic location) disadvantaged in accessing digital resources? This is an exploratory study and adopts a descriptive approach. Results: The main results of the study reveal that most students have access to a mobile phone, which is also the main means of accessing the internet. On the other hand, socioeconomic conditions and geographic location have an impact on the ownership of and access to digital technologies and the internet. Conclusion: The study data reveal that inequalities in access to digital technologies exist. On the other hand, socioeconomic conditions and geographical location have an influence on digital exclusion.